'Puisé Aux Meilleures Sources': Textual and Visual Strategies of Mid-19th-Century Architectural Historiography in Belgium. Issue 1 (24th December 2015) - Van Impe, Ellen
Abstract : The Belgian architectural world of the 19th century has been considered a fascinating though little studied crossroads of influences. The same could be said of the architectural historiography of Belgium, which only established its independence from its powerful neighbours in 1830. Two of its canonical architectural historical publications, the Histoire de l'architecture en Belgique by A.G.B. Schayes (1808–59) and the Histoire de l'influence italienne sur l'architecture dans les Pays-Bas by Auguste Schoy (1838–85), represent two different ways of dealing with textual and visual material. This emerges from a precise analysis of context, authorial voice, use of sources and illustration media and relation to repertories of images such as private print collections. Typical of Schayes's voice are the sparsely expressed personal appreciations and the many references to archives, literature and in situ observations, as if to prove every statement in word or image. Meanwhile, he rarely refers to his authoritative position as 'national archéologue' (as curator of the first national collection of antiquités ), nor to his collection of prints and engravings. Schoy, on the contrary, does not shy from emitting personal opinions and boasting about his precious collection, his broad knowledge of rare manuscripts and collections and his in situ explorations of buildings. The fact that Schoy's text did not make it into the accepted references in twentieth-century architectural histories in Belgium, whereas Schayes's did, reveals much about how the discipline was formed and which methodological selections were made during its formative period.